2015
DOI: 10.1111/eea.12287
|View full text |Cite
|
Sign up to set email alerts
|

Tracing dietary origins of aphids and the predatory beetle Propylea japonica in agricultural systems using stable isotope analyses

Abstract: Tracing dietary origins of the predatory beetle Propylea japonica (Thunberg) (Coleoptera: Coccinellidae) aids understanding their roles in the food web and provides information to develop strategies for effective conservation in agroecosystems comprised of wheat [Triticum aestivum L. (Poaceae)], cotton [Hirsutum spp. (Malvaceae)], and maize [Zea mays L. (Poaceae)]. Intrinsic markers of carbon and nitrogen stable isotope ratios (δ13C and δ15N) in P. japonica need to be developed to ascertain the source(s) of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Soybean aphid 13 C and 15 N values were significantly positively correlated with those of their host plants ( Figure 2 a), being slightly enriched (slope = 1.1), on average, relative to the plant in terms of 15 N, and depleted (slope = 0.8) in terms of 13 C. Previous studies have also found scaling of bulk 15 N between aphids and host plants, though the direction of scaling varies among studies [ 24 , 36 , 37 , 38 , 39 ]. Importantly, the observed signal of isotopic congruence between the soybean aphids and buckthorn host plants suggests stable isotopes, particularly 15 N, could be used to distinguish the origins of spring colonizers of soybean.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Soybean aphid 13 C and 15 N values were significantly positively correlated with those of their host plants ( Figure 2 a), being slightly enriched (slope = 1.1), on average, relative to the plant in terms of 15 N, and depleted (slope = 0.8) in terms of 13 C. Previous studies have also found scaling of bulk 15 N between aphids and host plants, though the direction of scaling varies among studies [ 24 , 36 , 37 , 38 , 39 ]. Importantly, the observed signal of isotopic congruence between the soybean aphids and buckthorn host plants suggests stable isotopes, particularly 15 N, could be used to distinguish the origins of spring colonizers of soybean.…”
Section: Resultsmentioning
confidence: 71%
“…For example, geographic variation in stable isotope composition of deuterium and 13 C has been utilized to make inferences about monarch butterfly ( Danaus plexippus L.) migration from overwintering sites in Mexico to summer habitats across a broad expanse of North America [ 18 , 19 ]. Within agricultural landscapes, variation in diet revealed by stable isotopes of 13 C and 15 N has been used to track movement of herbivores and predators among crop types [ 20 , 21 , 22 , 23 , 24 ]. The stable isotope composition of an organism derives from (1) the maternal contribution to its biomass; (2) the isotopic compositions of the proteins, lipids, water, and sugars in its diet; (3) N-turnover within the organism; (4) energy demands of the organism; and (5) background isotopic signatures, as a function of latitude/longitude, altitude, humidity, habitat type, and the myriad random effects of life in a heterogeneous landscape [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, there has been little research on stable isotopes as provenance markers in sap‐sucking insects (e.g. ) and none on the family Pentatomidae. Of note is that the intra‐population δ 2 H variation was less than observed for other entomological isotope studies and the intra‐country variation was generally consistent across the reference data‐set.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ye et al (2014), peanut was a more effective refuge to sustain Bt-susceptible bollworm individuals and reduce the risk of development of a Btresistant biotype. Ouyang et al (2015) traced dietary origins of the predatory beetle Propylea japonica (Thunberg) (Coleoptera: Coccinellidae) based on the values of δ 15 N and δ 13 C, in order to understand their roles in the food web and provide information to develop strategies for effective conservation in agroecosystems.…”
Section: Discussionmentioning
confidence: 99%